2007
DOI: 10.1038/sj.bjc.6603546
|View full text |Cite
|
Sign up to set email alerts
|

Immunostaining of thymidylate synthase and p53 for predicting chemoresistance to S-1/cisplatin in gastric cancer

Abstract: High expression of thymidylate synthase (TS) and inactivation of p53 are allegedly associated with chemoresistance. The authors evaluated TS and p53 expression in gastric cancer treated with neoadjuvant S-1/cisplatin chemotherapy. Paraffin sections of pretreatment biopsy and surgical specimens from 41 gastric cancers were immunostained for TS and p53 protein after appropriate antigen retrieval. Fifty-one cases without neoadjuvant chemotherapy were also studied. In the pretreatment biopsies, high expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 31 publications
0
18
3
Order By: Relevance
“…Nuclear p53 correlated with disease-specific (P ¼ 0.028) and overall survival (Po0.001) in the primary surgery group but no significant associations were observed in the neoadjuvant group. This is in contrast to a study by Kamoshida et al (2007), who showed that p53 expression was correlated with resistance to chemotherapy in gastric cancer patients.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Nuclear p53 correlated with disease-specific (P ¼ 0.028) and overall survival (Po0.001) in the primary surgery group but no significant associations were observed in the neoadjuvant group. This is in contrast to a study by Kamoshida et al (2007), who showed that p53 expression was correlated with resistance to chemotherapy in gastric cancer patients.…”
Section: Discussioncontrasting
confidence: 54%
“…p53 is a transcription factor that binds to specific sites in the regulatory regions of p53-responsive genes, leading to cellular events such as growth arrest (perhaps to allow for DNA repair), or where there is extensive DNA damage to initiate apoptosis. p53 expression is common in gastro-oesophageal cancer and may influence response to chemotherapy (Kamoshida et al, 2007).…”
mentioning
confidence: 99%
“…There are only very rare data of p53 and TS in the neoadjuvant setting. Kamoshida et al demonstrated in gastric cancer neoadjuvantly treated with S-1/cisplatin chemotherapy that high expression of TS and/or p53 in the pre-treatment biopsies predicted chemoresistance [40] . Other investig ators [41] were not able to find any cor relation between p53 and either TS or tumor regression.…”
mentioning
confidence: 99%
“…The analysis showed that postoperative adjuvant chemotherapy with S-1 alone significantly improved postoperative survival in patients with stage II/III gastric cancer who had undergone D2 gastrectomy. Although the overall anticancer effect was signifi cant, anticancer effects in individual cases were not uniform, and a certain number of patients showed chemoresistance to S-1-based chemotherapy [18]. Thus, a novel factor that can predict response to S-1-based chemotherapy is needed.…”
Section: Discussionmentioning
confidence: 99%